Des Suds vers le Grand Nord : recomposition des mobilités et des identités urbaines post-soviétiques - Hohmann, Sophie (Espace populations sociétés, 2021)
The Russian Arctic accounts for about 40% of the world’s Arctic population and indigenous peoples now account for only 5% of its total population. Russia is the most advanced in terms of urbanization of the whole Arctic. The settlement process has been marked by Soviet history and its paradoxes but they are also transformed into a transnational logic. This complex story of the construction of the most populated cities of the Arctic invites to decipher the urban identities, by investigating history of mobilities and urbanity’s construction with populations coming from different regions and formely Soviet republics, including Central Asia and the Southern Caucasus.This paper analyzes the link between recent mobility and that experienced during the Soviet era is shaped and embedded into reticular ties and how these new mobilities participate in the construction of multicultural identities. It shows how these economic migrants, mostly from former Soviet Muslim countries, will take advantage of the end of Sovietism and of de-secularization to reshape their religious identity around the community in a region which until now had not experienced this meeting. L’Arctique russe représente environ 40 % de la population de tout l’espace Arctique, et les peuples autochtones ne constituent que 5 % de sa population. La Russie est aussi la région arctique la plus urbanisée. Les processus de peuplement urbain ont été marqués par l’histoire soviétique et ses paradoxes, mais ils se transforment aussi dans une logique transnationale. Cette histoire complexe de la construction de villes les plus peuplées et les plus industrialisées de l’Arctique invite à s’intéresser aux identités urbaines, à l’histoire des mobilités et à la construction d’une citadinité arctique caractérisée par l’afflux croissant de populations originaires de différentes régions et républiques anciennement soviétiques, dont l’Asie centrale et le Caucase du Sud. Cet article analyse le lien entre les mobilités de l’époque soviétique et les plus récentes, et ...